Saranchinaite, Na2Cu(SO4)2, a new exhalative mineral from Tolbachik volcano, Kamchatka, Russia, and a product of the reversible dehydration of kröhnkite, Na2Cu(SO4)2(H2O)2. (28th February 2018) - Siidra, Oleg I.; Lukina, Evgeniya A.; Nazarchuk, Evgeniy V.; Depmeier, Wulf; Bubnova, Rimma S.; Agakhanov, Atali A.; Avdontseva, Evgeniya Yu.; Filatov, Stanislav K.; Kovrugin, Vadim M.
ABSTRACT: The new mineral saranchinaite, ideally Na2 Cu(SO4 )2, was found in sublimates of the Saranchinaitovaya fumarole, Naboko Scoria Cone, Tolbachik volcano, Kamchatka, Russia. Its discovery and study has enabled the characterization of the thermal decomposition of kröhnkite and provided an insight into the high-temperature behaviour of other kröhnkite-type materials. Saranchinaite is monoclinic, P 21, a = 9.0109(5), b = 15.6355(8), c = 10.1507(5) Å, β = 107.079(2)°, V = 1367.06(12) Å 3, Z = 8 and R 1 = 0.03. Saranchinaite is a unique mineral in that two of its four independent Cu sites display a very unusual Cu 2+ coordination environment with two weak Cu–O bonds of 2.9–3.0 Å, resulting in [4+1+2] CuO7 polyhedra. Each of the Cu-centred polyhedra shares common corners with SO4 tetrahedra resulting in a [Cu4 (SO4 )8 ] 8– framework with a complex channel system occupied by Na atoms. Saranchinaite is sensitive to moisture and transforms into kröhnkite within one week when exposed to open air at 87% relative humidity and 25°C. High-temperature X-ray diffraction studies were performed for both kröhnkite (from La Vendida mine, Antofagasta Region, Chile) and saranchinaite. During thermal expansion kröhnkite retains its strongly anisotropic character up to its full dehydration and the formation of saranchinaite at 200°C, which then transforms back into kröhnkite after exposure to open air. The thermal expansion of saranchinaite is more complex than that of kröhnkite. Saranchinaite is stable up to 475°C with subsequent decomposition into tenorite CuO, thénardite Na2 SO4 and unidentified phases.